Pseudo-beer belly disguised and presenting as inguinal hernia swelling: a case of massive retroperitoneal liposarcoma - Xie, Junfeng; Xi, Kexing; Ye, Baolong; Wang, Yangbiao; Liu, Hongquan; Xiao, Hefang (Frontiers in Medicine, 2025)
BackgroundLiposarcoma, a rare malignancy accounting for 1% of all cancers, constitutes 9.8–16% of soft tissue sarcomas. The retroperitoneum and extremities are primary sites of occurrence. Retroperitoneal liposarcoma (RLS), originating in retroperitoneal adipose tissue near the kidneys and mesentery, represents 0.07–0.2% of all tumors. Giant RLS is uncommon, and its presentation via inguinal herniation is exceedingly rare.Case descriptionA 43-year-old male presented with progressive right inguinal swelling over one year, initially diagnosed as an irreducible inguinal hernia. Physical examination revealed a non-pulsatile, soft inguinal mass persisting in supine position. Due to the patient’s abdominal obesity and atypical resilience of the mass, abdominal computed tomography (CT) was performed, identifying a large fatty lesion (25 × 22 × 32 cm) in the right abdomen and pelvis with septations and dense areas. Exploratory laparotomy revealed a lobulated, encapsulated retroperitoneal tumor adherent to the right kidney, retroperitoneal vasculature, and left ureter, with a nodule extending into the inguinal canal. En bloc resection and hernia repair were performed. Histopathology confirmed well-differentiated liposarcoma (WDLS) with MDM2/CDK4 overexpression and MDM2 amplification via fluorescence in situ hybridization (FISH). No recurrence was observed during follow-up (3–12 months postoperatively).ConclusionIn obese patients with abdominal obesity and irreducible inguinal herniation lacking obstructive symptoms, retroperitoneal tumors should be considered. Imaging (CT/MRI) and molecular testing (MDM2 FISH) are critical for differential diagnosis. Complete surgical excision with safe margins remains the cornerstone of management, followed by rigorous surveillance.